Case Report: Extrapulmonary tuberculosis presenting as multiple caseous pericardial masses - Juan Wang; Run Zhang; Zhengliang Li; Hui Fang; Wenzhong Zhang (Frontiers in Cardiovascular Medicine)
The diagnosis of tuberculous pericarditis presenting as a hemorrhagic pericardial effusion is not difficult to make, but the presence of multiple pericardial masses in tuberculous pericarditis is uncommon. The article reports a 55-year-old Asian woman with a 10-day history of fever, chest tightness and shortness of breath. Laboratory investigations revealed an elevated C-reactive protein and erythrocyte sedimentation rate, and echocardiography showed a small amount of pericardial effusion associated with multiple pericardial caseous masses (up to approximately 2.4 cm × 6.9 cm) without pericardial constriction. Ten ml of bloody pericardial effusion was punctured and sent for pathology without malignant cells, and malignant mesothelioma was excluded in combination with PET-CT results. The diagnosis of extrapulmonary tuberculosis was finally confirmed by a positive Mantoux test and positive tuberculosis immunoreactivity, and the patient is now receiving standardized anti-tuberculosis treatment in a specialist hospital. Nowadays, the diagnosis of tuberculous pericarditis is not difficult, but the symptoms of a concomitant giant mass are rare, and its nature and treatment options (including drugs or surgery) are worth exploring.